2020
DOI: 10.1007/s40119-020-00185-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography: Current Applications for the Assessment of Coronary Artery Disease and Guidance of Percutaneous Coronary Interventions

Abstract: Introduction Coronary angiography (CAG) is the standard modality for assessment of coronary stenoses and intraprocedural guidance of percutaneous coronary interventions (PCI). However, the limitations of CAG are well recognized. Intracoronary imaging (ICI) can potentially overcome these limitations. Intravascular ultrasound (IVUS) and optical coherence tomography (OCT) are the main ICI techniques utilized in clinical practice. Aim This narrative literature review addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…Meanwhile, when the no-reflow occurred, an aggressive dilation strategy should not be taken. Optimal stent expansion gained by postdilation, which is related to a better prognosis, has been confirmed by multiple studies and included in the PCI recommendation consensus (18)(19)(20)(21). However, overexpansion or oversize of stent caused by excessive postdilation has been increasing recently, but it has been less studied.…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, when the no-reflow occurred, an aggressive dilation strategy should not be taken. Optimal stent expansion gained by postdilation, which is related to a better prognosis, has been confirmed by multiple studies and included in the PCI recommendation consensus (18)(19)(20)(21). However, overexpansion or oversize of stent caused by excessive postdilation has been increasing recently, but it has been less studied.…”
Section: Discussionmentioning
confidence: 95%
“…While OCT may provide better image resolution of the coronary arteries, IVUS has greater imaging penetration than OCT, where large lipid-rich plaques may impair the ability to image the vessel border with OCT. [136] OCT requires contrast (often iodine-based), [137] which increases the risk of contrast induced nephropathy. Alternative OCT contrasts such as dextran may help avoid acute kidney injury.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Alternative OCT contrasts such as dextran may help avoid acute kidney injury. [138] Contrast induced nephropathy [136] is a poor prognostic factor that often delays hospital discharge and increases costs. [139] In short, OCT may be superior to IVUS in assessing the cause of stent failure, calcific coronary disease, and MINOCA.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Its higher resolution undoubtedly can confirm findings such as plaque erosion or calcified nodule which may cause AMI and usually are not visible on both conventional angiography and IVUS. Howbeit, it should be emphasized that OCT also has several drawbacks [37]. First, its greater resolution as compared to IVUS comes with a lower penetration depth.…”
Section: Etiology Of Minocamentioning
confidence: 99%
“…An OCT study including 23 patients found that those with Takotsubo cardiomyopathy have high plaque vulnerability [42]. Howbeit, it should be emphasized that OCT also has several drawbacks [37]. First, its greater resolution as compared to IVUS comes with a lower penetration depth.…”
Section: Etiology Of Minocamentioning
confidence: 99%